Analisis Natrium Siklamat Pada Minuman Sirup Varian Rasa Di Wilayah Kecamatan Kertak Hanyar - M. Awaluddin Padjrin; Najwi Hasani; Daipadli (JCPS (Journal of Current Pharmaceutical Sciences), 2025)
The addition of sodium cyclamate is commonly found in flavored syrup beverages in Indonesia and often exceeds BPOM’s limits. Excessive consumption over time may pose health risks. This study aims to detect sodium cyclamate, determine its concentration in flavored syrup beverages sold in Kertak Hanyar, and validate the analytical method used. Qualitative precipitation tests and quantitative UV-Vis spectrophotometry were employed. Four samples were analyzed, showing that three tested positive in the qualitative test, while all contained sodium cyclamate in the quantitative analysis, with concentrations ranging from 71.35 to 152.43 mg/kg. The discrepancy is likely due to the higher detection limit of the precipitation test, making it less sensitive to low concentrations. Method validation showed good performance, with an r-value of 0.9954, LOD and LOQ of 1.5405 mg/L and 5.1351 mg/L, RSD from 0 to 0.4773%, and recovery between 84.76% and 92.86%. The method met validation criteria, including linearity, detection capability, precision, and accuracy. In conclusion, sodium cyclamate levels in all samples were within BPOM’s safety limit of 250 mg/kg, ensuring their safety for consumption, while the analytical method was validated for determining sodium cyclamate using UV-Vis spectrophotometry.